Teaching and Generalizing Pretend Play in Children with Autism Using Video Modeling and Matrix Training†. (29th May 2015) - MacManus, Cormac; MacDonald, Rebecca; Ahearn, William H.
<x xml:space="preserve">Abstract</x> Children with autism spectrum disorder often lack play skills. Video modeling has been effective in producing play; however, this play is often lacking in novelty. The purpose of the present study was to combine video modeling and matrix training to teach children with autism to engage in sequences of play with 30 vocalizations and 40 actions. Matrix training was used in an attempt to enhance generalization, specifically in recombining elements of play across play scenarios. Three participants were trained on three play scenarios for three play sets and materials using video modeling. Play scenarios were arranged in a 3‐dimensional matrix, which also depicted the possible recombined sequences that could emerge. Probes were then conducted to determine whether different combinations of play would occur. Results for all participants showed that after training on three video modeling play scenarios, learned vocalizations and actions were recombined across previously unlearned combinations of play sets and materials. Results also showed that after video modeling began, novel play that was not seen in baseline sessions emerged for all participants. Copyright © 2015 John Wiley & Sons, Ltd.